Method for improving plasticity of TiAl-based alloy
By applying tensile or compressive stress loads lower than the eutectomy transition temperature in the titanium-aluminum-based alloy, creep deformation is achieved and deformation twins is formed, which solves the problem of poor plasticity in the high temperature of titanium-aluminum-based alloy and significantly improves its high temperature extension Long ratio and maintain strength.
Patent Information
- Application Number
- CN202411413578.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
The poor plasticity and fracture toughness of titanium-aluminum-based alloys at room temperature and high temperatures have resulted in limited application in the aerospace field. It is difficult for existing heat treatment and composite materials processes to significantly improve their high-temperature plasticity without reducing their strength.
By heating the TiAl-based alloy material to a temperature range below the eutectonic transition temperature (Te) (150°C to 450°C) and applying tensile or compressive stress loads, the insulation time is at least 5 hours, and the load is controlled at 40% of the yield strength. ~60%, to achieve creep deformation and form a large number of deformation twins, thereby significantly improving its high temperature elongation.
Without reducing the strength, the high-temperature elongation of TiAl-based alloy is significantly improved. The elongation of the treated material under (Te-300)℃ is increased by 4 to 61.6 times, while maintaining the high-temperature strength is not low intensity before treatment.
Smart Images

Figure CN119287284A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium-aluminum intermetallic compound processing, and in particular relates to a method for improving the plasticity of a TiAl-based alloy. Background Art
[0002] As a lightweight high-temperature structural material, titanium-aluminum-based alloy has many advantages such as high specific strength and specific stiffness, corrosion resistance, wear resistance, excellent oxidation resistance, and outstanding creep and fatigue resistance, making it an ideal lightweight high-temperature structural material in the aerospace field. However, the shortcomings of TiAl intermetallic compounds, such as poor room temperature plasticity and fracture toughness, and difficulty in high-temperature plastic forming, have become an important bottleneck for their application.
[0003] The room temperature elongation of titanium aluminum alloys prepared by conventional methods (ingot metallurgy and powder metallurgy) is usually less than 1%, and the elongation at 800°C is less than 2%. Even after heat treatment or preparation of composite materials, the elongation of the alloy is limited, but it is accompanied by a decrease in strength. For example, after hot deformation treatment of cast titanium aluminum alloys with full lamellar structure, the high temperature elongation of the alloy is significantly improved, but the high temperature strength is reduced. Although PST titanium aluminum has high high temperature plasticity, its preparation process is more complicated and the process control is more difficult. In recent years, it has been reported that after a specific heat treatment process is used to make the alloy have a new microstructure (three-phase three-state and three-phase two-state junction), the elongation of the alloy at 800°C can reach about 30%, but the strength of the alloy is also significantly reduced compared to before treatment. In ZL202211126445.5, after small deformation forging treatment, the strength and elongation of the 3D printed titanium aluminum alloy at 800°C are improved, but its elongation is only 11.5-12%. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for significantly improving the high-temperature plasticity of TiAl-based alloys without reducing the strength. The elongation of the titanium aluminum alloy treated by the method of the present invention at (Te-300)°C is increased to 7% to 61.6%, which is 4 to 61.6 times higher than that before treatment, while maintaining the strength not lower than that before treatment.
[0005] In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0006] The present invention provides a method for improving the plasticity of a TiAl-based alloy. The TiAl-based alloy material is heated to (Te-450) to (Te-150)°C and kept warm for ≥30 minutes, and then a tensile stress or a compressive stress load is applied. The temperature is kept warm and the load is kept warm for ≥5 hours to obtain a treated TiAl-based alloy material. The tensile stress or the compressive stress load is 40% to 60% of the yield strength of the TiAl-based alloy material under corresponding temperature conditions.
[0007] In the present invention, Te is the eutectoid transformation temperature.
[0008] The method provided by the present invention, under the loading stress and temperature process conditions of the present invention, the material will undergo creep deformation, which is different from conventional plastic deformation in that the load applied by creep deformation is much lower than the yield strength of the material, and the material will only undergo plastic deformation under the action of temperature and load for a long time, that is, the strain rate in the entire deformation process is extremely low (less than 10 -6 / s), which is higher than the strain rate of conventional plastic deformation (greater than 10 -3 / s) is 3 orders of magnitude lower. Under such deformation conditions, a large number of deformation twins will be formed in the alloy. The present invention utilizes the strengthening effect of twins on the plasticity and strength of the alloy to achieve a significant increase in elongation while still ensuring that the strength is not reduced. Although in theory, conventional plastic deformation can also produce deformation twins in certain materials, it is necessary to ensure that the deformation is greater than 5%. However, in titanium-aluminum alloys, when deformed at 300°C below Te, the ultimate deformation of the alloy is usually less than 2%, that is, the strain condition for producing deformation twins has not been reached, and the material has already fractured and failed. Therefore, the scheme of prefabricating twins using conventional plastic deformation technology is not feasible in actual operation. Creep deformation at an ultra-low strain rate ensures that the plastic deformation can reach more than 5%, which provides a guarantee for the formation of deformation twins.
[0009] In the present invention, the heating and heat preservation temperature is selected to be 150°C to 450°C lower than the Te temperature of the TiAl-based alloy material, which can not only ensure that the material has a certain plasticity, but also ensure that the material does not undergo any phase change during the treatment process, thereby avoiding the uncertainty of material organization and performance caused by phase change. In addition, at this treatment temperature, the alloy is basically not oxidized, and there is no need to perform surface anti-oxidation treatment or vacuum treatment during the treatment process.
[0010] The essential difference between the present invention and the method of improving the plasticity of alloys by plastic deformation is that the load applied in the present invention is only 40% to 60% of the yield strength, that is, from the perspective of load, the alloy does not undergo plastic deformation, and even if plastic deformation occurs, its strain rate is much lower than the plastic deformation under conventional high stress; while the load applied by the plastic deformation process must be greater than the yield strength of the alloy, and its mechanism is to promote dynamic recrystallization and grain refinement of the alloy through plastic deformation, thereby improving plasticity. There is an essential difference between the two in the principle of improving plasticity.
[0011] In the method provided by the present invention, the applied load is 40% to 60% of the yield strength of the alloy under the corresponding temperature conditions, that is, the applied load needs to be determined according to the yield strength of the alloy under the corresponding temperature conditions, and the above corresponding temperature is the specific insulation temperature.
[0012] A preferred solution is to heat the TiAl-based alloy material to (Te-400) to (Te-250)° C., preferably (Te-300) to (Te-250)° C. The plasticity of the alloy is improved the most when the TiAl-based alloy material is heated to a temperature of 250 to 400° C., which is lower than the Te temperature of the TiAl-based alloy material, and then kept warm.
[0013] The preferred solution is to keep the temperature for 30 to 60 minutes. In the present invention, there is actually no need to control the holding time before the load is applied, as long as the material temperature and the furnace temperature are consistent and the overall temperature of the material is uniform. Of course, if it is too long, it will waste resources for industrial production.
[0014] In a preferred embodiment, the tensile stress or compressive stress load is 100 to 250 MPa.
[0015] The preferred solution is to keep the alloy warm for 5 to 35 hours. After the insulation and loading are completed, the load is removed and the alloy is cooled with the furnace. In the present invention, after applying tensile stress or compressive stress, the insulation time is relatively important. If the insulation time is less than 5 hours, the creep deformation of the alloy is small and the conditions for producing deformation twins are not met. If the insulation time is too long (greater than 35 hours), the creep deformation is too large. On the one hand, there is a limit to the number of twins. After the deformation exceeds 15%, the increase in the number of twins is not obvious. On the other hand, if the deformation is too large, it may cause the material to fracture and fail during the creep process.
[0016] In actual operation, the heat preservation and loading time is 5 to 35 hours, and the preferred heat preservation time is selected according to the material, temperature and load conditions.
[0017] In a preferred embodiment, the TiAl-based alloy material is selected from a powder metallurgy titanium-aluminum alloy material, an ingot metallurgy titanium-aluminum alloy material, and an additively manufactured titanium-aluminum alloy material.
[0018] Further preferably, the additively manufactured titanium-aluminum alloy material is an electron beam additively manufactured titanium-aluminum alloy material.
[0019] Further preferably, the TiAl-based alloy material is selected from a powder metallurgy titanium-aluminum alloy material having a near-γ structure or an electron beam additively manufactured titanium-aluminum alloy material having both a coarse γ structure and a fine dual-state structure.
[0020] In a preferred embodiment, when the TiAl-based alloy material is a powder metallurgy titanium-aluminum alloy material,
[0021] The TiAl-based alloy material is heated to (Te-300)°C, kept warm for 30 to 60 minutes, and then a tensile stress or a compressive stress load of 200 MPa is applied, and the temperature is kept warm for 25 to 35 hours, preferably 30 to 35 hours; or the TiAl-based alloy material is heated to (Te-300)°C, kept warm for 30 to 60 minutes, and then a tensile stress or a compressive stress load of 250 MPa is applied, and the temperature is kept warm for 5 to 8 hours.
[0022] When the TiAl-based alloy material is a powder metallurgy titanium-aluminum alloy material, and a tensile stress or a compressive stress load of 200 MPa is applied and the material is kept warm and loaded for 30 to 35 hours, the elongation is increased by 10.5 to 12 times.
[0023] A preferred solution is that when the TiAl-based alloy material is an electron beam additively manufactured titanium aluminum alloy material, the TiAl-based alloy material is heated to (Te-300)°C, kept warm for 30 to 60 minutes, and then a 200 MPa tensile stress or compressive stress load is applied, and the temperature is maintained for 25 to 30 hours, preferably 27.5 to 30 hours.
[0024] When the TiAl-based alloy material is an electron beam additively manufactured titanium aluminum alloy material and a tensile stress or compressive stress load of 200 MPa is applied, the elongation can be increased to 35% to 61.6% when the material is kept at a temperature and loaded for 27.5 h to 30 h, with an increase of 35 to 61.6 times.
[0025] In a preferred embodiment, the high temperature strength of the treated TiAl-based alloy material at (Te-300)°C is not lower than that of the alloy before treatment, and the elongation is 7% to 61.6%. The elongation is increased by 4 to 61.6 times. In the most preferred embodiment, the elongation can be increased to 35% to 61.6%.
[0026] Principles and advantages
[0027] Compared with traditional hot plastic deformation to improve the plasticity of titanium aluminum alloy, the present invention adopts lower temperature (150℃~450℃ lower than Te temperature, conventional plastic deformation is 200℃~300℃ higher than Te temperature); lower stress (40%~60% of yield strength, conventional plastic deformation stress must be higher than yield strength); longer time (5~35h, conventional plastic deformation is in seconds). Using the process of the present invention, the material is creep deformed instead of conventional plastic deformation. After creep, a large number of deformation twins are formed in the alloy. In theory, the enhancement effect of twins on the plasticity and strength of the material can be used to achieve a significant increase in elongation without reducing strength. Different from conventional plastic deformation methods that use recrystallization to improve the plasticity of the alloy, the significant softening effect caused by recrystallization is avoided.
[0028] The advantages are: (1) The temperature and stress of the processing process are relatively low, and the equipment requirements are lower than those of conventional plastic deformation methods; (2) The processing process does not require the material to be treated for oxidation resistance or to be processed in a vacuum environment; (3) The treated alloy can increase the plasticity by 4 to 61.6 times without reducing the strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 High temperature tensile curve of untreated powder metallurgy 4822 alloy at 800℃;
[0030] Figure 2 High temperature tensile curve of untreated electron beam additively manufactured 4822 alloy at 800°C;
[0031] Figure 3 High temperature tensile curve of the alloy after treatment in Example 1 at 800°C;
[0032] Figure 4 High temperature tensile curve of the alloy after treatment in Example 2 at 800°C;
[0033] Figure 5 High temperature tensile curve of the alloy after treatment in Example 3 at 800°C;
[0034] Figure 6 High temperature tensile curve of the alloy after treatment in Example 4 at 800°C;
[0035] Figure 7 High temperature tensile curve of the alloy after treatment in Example 5 at 800°C;
[0036] Figure 8 High temperature tensile curve of the alloy after treatment in Example 6 at 800°C;
[0037] Fig. 9 High temperature tensile curve of the alloy after treatment in Example 7 at 800°C;
[0038] Fig.10 High temperature tensile curve of the alloy after treatment in Comparative Example 1 at 800°C;
[0039] Fig.11 High temperature tensile curve of the alloy after treatment in Comparative Example 2 at 800°C. DETAILED DESCRIPTION
[0040] The following are preferred embodiments of the present invention, but not all embodiments. Without departing from the principle of the process innovation, any equivalent process transformation made by using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, shall be deemed as the patent protection scope of the present invention.
[0041] The following embodiments take powder metallurgy 4822 alloy (48% Ti, 48% Al, 2% Nb, 2% Cr) and electron beam additive manufacturing 4822 alloy as examples, whose Te is 1100°C. Of course, in addition to the powder metallurgy 4822 alloy, the present invention also tried titanium aluminum alloys with other compositions, all of which conform to the rules of the present invention. However, since the present invention has conducted systematic experiments on the powder metallurgy 4822 alloy, the powder metallurgy 4822 alloy is taken as an example.
[0042] The yield strength of the powder metallurgy 4822 alloy not treated by the present invention at 800° C. is 320 MPa, the tensile strength is 392 MPa, and the elongation is 1.5%; the yield strength of the electron beam additively manufactured 4822 alloy at 800° C. is 506 MPa, the tensile strength is 577 MPa, and the elongation is 1.0%.
[0043] Example 1
[0044] The 4822 titanium aluminum alloy prepared by powder metallurgy was heated to 800℃ and kept warm for 30 minutes, then a tensile stress of 200MPa was applied and kept warm for 25 hours, the load was removed, and the alloy was cooled in the furnace. The yield strength of the alloy obtained at 800℃ was 367MPa, the tensile strength was 453MPa, and the elongation was 11.36%. The yield strength and tensile strength of the alloy before treatment were increased by 47MPa and 62MPa respectively, and the elongation was 7.5 times that before treatment.
[0045] Example 2
[0046] The 4822 titanium aluminum alloy prepared by powder metallurgy was heated to 800℃ and kept warm for 45 minutes, then a tensile stress of 200MPa was applied and kept warm for 30 hours, the load was removed, and the alloy was cooled in the furnace. The yield strength of the alloy obtained at 800℃ was 370MPa, the tensile strength was 453MPa, and the elongation was 18.0%. The yield strength and tensile strength of the alloy before treatment were increased by 50MPa and 62MPa respectively, and the elongation was 12 times that before treatment.
[0047] Example 3
[0048] The 4822 titanium aluminum alloy prepared by powder metallurgy was heated to 800℃ and kept warm for 60 minutes, then a tensile stress of 200MPa was applied and kept warm for 35 hours, the load was removed, and the alloy was cooled in the furnace. The yield strength of the alloy obtained at 800℃ was 385MPa, the tensile strength was 448MPa, and the elongation was 15.8%. The yield strength and tensile strength of the alloy before treatment were increased by 65MPa and 56MPa respectively, and the elongation was 10.5 times that before treatment.
[0049] Example 4
[0050] The 4822 titanium aluminum alloy prepared by powder metallurgy was heated to 800℃ and kept warm for 30 minutes, then a tensile stress of 250MPa was applied and kept warm for 8 hours, then the load was removed and the alloy was cooled in the furnace. The yield strength of the alloy obtained at 800℃ was 382MPa, the tensile strength was 458MPa, and the elongation was 6.6%. The yield strength and tensile strength of the alloy before treatment were increased by 62MPa and 66MPa respectively, and the elongation was 4.4 times that before treatment.
[0051] Example 5
[0052] The 4822 titanium aluminum alloy prepared by electron beam additive manufacturing was heated to 800℃ and kept warm for 30 minutes, then 200MPa tensile stress was applied and kept warm for 25 hours, then the load was removed and the furnace was cooled. The yield strength of the alloy obtained at 800℃ was 546MPa, the tensile strength was 633MPa, and the elongation was 7.1%. The yield strength and tensile strength of the alloy before treatment were increased by 40MPa and 56MPa respectively, and the elongation was 7.1 times that before treatment.
[0053] Example 6
[0054] The 4822 titanium aluminum alloy prepared by electron beam additive manufacturing was heated to 800℃ and kept warm for 40 minutes, then 200MPa tensile stress was applied and kept warm for 30 hours, then the load was removed and the furnace was cooled. The yield strength of the alloy obtained at 800℃ was 528MPa, the tensile strength was 597MPa, and the elongation was 61.6%. The yield strength and tensile strength of the alloy before treatment were increased by 12MPa and 20MPa respectively, and the elongation was 61.6 times that before treatment.
[0055] Example 7
[0056] The 4822 titanium aluminum alloy prepared by electron beam additive manufacturing was heated to 800℃ and kept warm for 30 minutes, then 200MPa tensile stress was applied and kept warm for 27.5h, then the load was removed and the furnace was cooled. The yield strength of the alloy obtained at 800℃ was 539MPa, the tensile strength was 608MPa, and the elongation was 35%. The yield strength and tensile strength of the alloy before treatment were increased by 33MPa and 31MPa respectively, and the elongation was 35 times that before treatment.
[0057] Comparative Example 1
[0058] The 4822 titanium aluminum alloy prepared by powder metallurgy was heated to 1000℃ and kept warm for 30 minutes, then a tensile stress of 200MPa was applied and kept warm for 10 hours, the load was removed, and the alloy was cooled in the furnace. The yield strength of the alloy obtained at 800℃ was 343MPa, the tensile strength was 438MPa, and the elongation was 1%. The yield strength and tensile strength of the alloy before treatment were increased by 23MPa and 46MPa respectively, and the elongation was reduced.
[0059] Comparative Example 2
[0060] The 4822 titanium aluminum alloy prepared by electron beam additive manufacturing was heated to 800℃ and kept warm for 45 minutes, then a tensile stress of 250MPa was applied and kept warm for 4 minutes, then the load was removed and the alloy was cooled in the furnace. The yield strength of the alloy obtained at 800℃ was 513MPa, the tensile strength was 593MPa, and the elongation was only 3.8%. The yield strength and tensile strength of the alloy before treatment were increased by 7MPa and 16MPa respectively, and the elongation was only 3.8 times that before treatment.
Claims
1. A method for improving the plasticity of a TiAl-based alloy, characterized in that: The TiAl-based alloy material is heated to (Te-450)-(Te-150)°C and kept warm for ≥30 minutes, and then a tensile stress or a compressive stress load is applied, and the temperature is kept warm and loaded for ≥5 hours to obtain a treated TiAl-based alloy material; the tensile stress or the compressive stress load is 40%-60% of the yield strength of the TiAl-based alloy material under the corresponding temperature conditions.
2. A method for improving the plasticity of a TiAl-based alloy according to claim 1, characterized in that: Heat the TiAl-based alloy material to (Te-400) ~ (Te-250) ° C and keep it warm for 30 to 60 minutes.
3. A method for improving the plasticity of a TiAl-based alloy according to claim 1 or 2, characterized in that: The tensile stress or compressive stress load is 100 to 250 MPa; Keep warm and load for 5 to 35 hours.
4. A method for improving the plasticity of a TiAl-based alloy according to claim 1 or 2, characterized in that: The TiAl-based alloy material is selected from a powder metallurgy titanium-aluminum alloy material, an ingot metallurgy titanium-aluminum alloy material, and an additively manufactured titanium-aluminum alloy material.
5. A method for improving the plasticity of a TiAl-based alloy according to claim 4, characterized in that: The TiAl-based alloy material is selected from a powder metallurgy titanium-aluminum alloy material with a near-γ structure or an electron beam additively manufactured titanium-aluminum alloy material having both a coarse γ structure and a fine dual-state structure.
6. A method for improving the plasticity of a TiAl-based alloy according to claim 4, characterized in that: When the TiAl-based alloy material is a powder metallurgy titanium-aluminum alloy material, the TiAl-based alloy material is heated to (Te-300)°C, kept warm for 30 to 60 minutes, and then a tensile stress or compressive stress load of 200 MPa is applied, and the temperature is kept warm for 25 to 35 hours. Alternatively, the TiAl-based alloy material is heated to (Te-300)°C, kept warm for 30 to 60 minutes, and then a tensile stress or compressive stress load of 250 MPa is applied, and the temperature is kept warm for 5 to 8 hours.
7. A method for improving the plasticity of a TiAl-based alloy according to claim 4, characterized in that: When the TiAl-based alloy material is used for electron beam additive manufacturing of titanium-aluminum alloy material, the TiAl-based alloy material is heated to (Te-300)°C, kept warm for 30 to 60 minutes, and then a tensile stress or a compressive stress load of 200 MPa is applied, and the temperature is kept and loaded for 25 to 30 hours.
8. A method for improving the plasticity of a TiAl-based alloy according to claim 1 or 2, characterized in that: The high temperature strength of the treated TiAl-based alloy material under (Te-300)°C condition is not lower than the high temperature strength of the alloy before the treatment, and the elongation is 7% to 61.6%.
Citation Information
Patent Citations
Process for improving high-temperature strong plasticity of titanium-aluminum-based alloy
CN115679231A